Analysis and Research of the Nonlinear Dynamic Performance of a Certain Type Harmonic Gear Drive System - Hao Junwen (Jixie chuandong)
Taking the MATLAB software as platform,on the premise of considering influence of nonlinear factor such as gear backlash etc on the dynamic performance of system,the digital simulation model of harmonic gear drive is built. The simulation analysis is carried out,the influence rules of the main parameters such as sticky friction coefficient,gear backlash,rigidity coefficient etc on the performance of overall system are confirmed. At the same time,the comparative analysis between simulation data and corresponding experimental data is carried out,to analyze the problem appears in the application of a harmonic gear drive.